Biodiversity: Research and Conservation reaches volume 50! Looking back and forward - Jackowiak, Bogdan; Celka, Zbigniew; Obarska, Elżbieta (Biodiversity: Research and Conservation, 2018)
Biodiversity: Research and Conservation, published at the Adam Mickiewicz University in Poznań (Poland), is open for the authors from the whole world and attracts a growing interest among researchers and readers. The data presented in this article show that this journal is read in a growing number of countries. It reaches readers mostly through its online version, but it is still published also in the traditional paper form, with the possibility of including colour photographs and figures.